Peranan Supervisi Kepala Madrasah terhadap Kreativitas Guru dalam Pengelolaan Kelas di MTsN 1 Gunungkidul - Hamid Abdul Basit (Jurnal Pendidikan Madrasah, 2021)
This research aims to find out the role of madrasah head supervision in increasing teacher creativity in managing the classroom. This research was conducted at MTsN 1 Gunungkidul with the object of 25 teachers consisting of 23 teachers with civil servant status and 2 Non-civil servant teachers. The study uses the Class Action method through two cycles that include planning, observation, action, and reflection activities. The results showed forms of teacher creativity in classroom management including classroom planning, classroom organizing, classroom direction, classroom coordination, classroom communication, and classroom control. While the role of supervision of madrasah heads on teacher creativity in classroom management is as a leader, as a giver of training and guidance, and as a motivation for teaching activities for teachers.